Design and experimental evaluation of yoked hand-clutching for a lever drive chair. - Sarigul-Klijn, Yasemin; Smith, Brendan W.; Reinkensmeyer, David J. (Assistive Technology, 2018)
Lever-drive wheelchairs lower physical strain but are less maneuverable than push-rim wheelchairs. Here, we study a possible solution in which the user simultaneously actuates clutches mounted between the levers and wheels each stroke via a clutch handle attached to one lever; this solution is of particular interest for user groups with only one functional hand. First, to demonstrate maneuverability, we show how this “yoked clutch” allows an experienced user to maneuver a constrained space. Then, we compared the difficulty of learning a yoked clutch chair to a conventional lever-drive transmission (i.e. a one-way bearing). Twenty-two unimpaired novice adults navigated a figure-eight track during six training sessions over two weeks. Participant mean speed improved roughly 60% for both chairs, with similar exponential improvement time constants (3 days) and final speeds. However, speed improvement mostly took place overnight rather than within the session for hand-clutching, and the physiological cost index was also about 40% higher. These results indicate that while hand-clutching is no more difficult to learn than a lever-drive, it is reliant on overnight improvement. Also, its increased maneuverability comes with decreased efficiency. We discuss how the yoked clutch may be particularly well suited for individuals with stroke during inpatient rehabilitation.